Numerical Study on Enhancing Photovoltaic Panel Efficiency Through Heat Exchanger Cooling with Al₂O₃ Nanofluid - Yamunan Manimaran; M A Elfaghi, Abdulhafid; Abdoulhdi A. Borhana Omran; Mostafa Abobaker (International Journal of Integrated Engineering, 2026)
This study offers a numerical assessment of the thermal, electrical, and hydraulic performance of a monocrystalline photovoltaic (PV) module featuring a rear-mounted copper heat exchanger and cooled with Al₂O₃ nanofluids at concentrations of 2% and 4% across Reynolds numbers (Re) ranging from 1500 to 2600. The findings indicate that both nanofluids decreased PV surface temperatures relative to the uncooled baseline, resulting in enhanced electrical conversion efficiency. The 2% concentration exhibited consistent thermal reduction from 333.44° C to 326.48°C and constant efficiency improvements from 12.88% to 13.30% alongside predicted friction factor behaviour, reducing from 0.0427 to 0.02888. Conversely, the 4% nanofluid attained enhanced cooling which result in 301.90 °C and optimal efficiency of 14.78% at low Reynolds numbers, yet suffered significant performance decline at elevated flow rates, with temperatures surpassing the baseline and efficiencies plummeting to a mere 3.74%, due to heightened viscosity, nanoparticle agglomeration, and flow instabilities. These findings underscore the necessity of optimizing nanofluid concentration and flow rate to attain a balance of heat dissipation, efficiency improvement, and feasible pumping demands. The 2% concentration proves to be the most dependable choice for continuous PV cooling throughout various operating circumstances, whereas the 4% concentration may only be beneficial in low-flow scenarios. Future research must prioritize experimental validation, the examination of long-term nanoparticle dispersion stability under operational stresses, and an extensive techno-economic analysis to evaluate the viability of incorporating nanofluid-based cooling systems into large-scale solar energy installations.